A course in mathematical analysis vol 2, part 2 : differential equations - Goursat, Edouard (New York: Dover Publication, 1959)
This volume basically comprises: Equations of First, Higher Orders; Existence Theorems; Cauchy-Lipchitz Method; Linear and Non-Linear Differential Equations; Singular Integrals; Exceptional Initial Values; and Simultaneous Equations.
Includes bibliographical references: p. [291]-300.
ne 007/03/2018
Loans
Keywords: Calculus; Matrhematical analysis